Aspect of religious coping, element of neuroscience, al-Quran recital approaches and resilience among university students in the post-Covid-19 pandemic - Ab Rahman, Z.; Ahmad Faizuddin Ramli; Abdul Rauf Ridzuan; Miftachul Huda (Penerbit Universiti Kebangsaan Malaysia, 2024)
Aspect of religiosity, religious coping, element of neuroscience, al-Quran recital, and resilience approaches contain various elements needed by humankind, such as religious, social, economic, health, medical, scientific, political, and other aspects, as a guide for achieving prosperity in this life and the afterlife, reciting the al-Quran daily showers a person with continuous serenity, which is a very effective therapy for a person facing pressures in life. Recital Quran has a unique power to change an individual’s inappropriate behavior to appropriate behavior among post-COVID-19 university students during the post-COVID-19 Pandemic in Malaysia. The al-Quran also provides all the internal and external needs required by a person to face the various challenges of post-COVID-19 university students during the post-COVID-19 Pandemic in Malaysia. Reciting the al-Quran is not only advantageous to a person but listening to recitals can also provide serenity and blessings from Allah the Almighty.